The Study of Time Spent on Nursing Activities in Operating Room, Lampang Hospital - Udkunta, Kedsaraporn; Nantsupawat, Apiradee; Thungjaroenkul, Petsunee (Nursing Journal CMU, 2020)
The time spent on nursing activities is important information to nurse staffing. The purpose of this study was to analyze nursing activities according to the nursing needs of each type of patient and study the number of hours spent by nurses performing nursing activities for each type of patient in the operating room at Lampang Hospital.The sample were 8 registered nurses working in cardiac vascular and thoracic surgery departments at Lampang Hospital and 58 patients who received surgery services from the operating room at Lampang Hospital during the time of this study. The tools used in this study contains a dictionary of surgical nursing activities the content validity index of 0.80. And a recording of the amount of time that nursing personnel spend in nursing activities the interobserver reliability of 0.93. Applying the step of the nursing staffing planning process of Srisathidnarakul (2007). Patient classification according to the Patton (2002) concept. And patient classification based on nursing activities according to the Connor (1961). Data were analyzed using descriptive statistics. The result showed that Nursing activities of major patients total 39 activities and minor patients total 27 activities Time spent on nursing activities in major patients was 7 hours 11 minutes, with time spent on direct nursing activities was 5 hours 48 minutes. Time spent on indirect nursing activities was 1 hour 23 minutes. Time spent on nursing activities in minor patients was 2 hours 26 minutes, time spent on direct nursing activities was 1 hour 45 minutes and time spent on indirect nursing activities was 41.15 minutes The results of this study are basic information for managers to use as a basis for calculating staffing.